Réponses

  • Omnes
  • Modérateur confirmé
2014-02-05T22:32:42+01:00
Salut,

A = (3x -2)(6x +7) - (3x-2)(-2x+4) \\
A = (3x -2)[6x + 7 -(-2x+4)]\\
A = (3x -2)(6x + 7 +2x - 4]\\
A = (3x -2)(8x +3)\\

B = (6x -8)^{2} - (2x-3)^{2} \\
B = [6x -8 - (2x-3)][6x - 8 + 2x -3]\\
B = (6x - 8 -2x + 3)(6x - 8 + 2x - 3)\\
B = (4x - 5)(8x - 11)\\

C = (5x -8)^{2} + (5x - 8)\\
C = (5x -8)(5x - 8) + (5x - 8)*1 \\
C = (5x -8)(5x - 8 +1)\\
C = (5x - 8)(5x -7) \\
D = (2x + 7)^{2} -81 \\
D = (2x + 7)^{2}  - 9^{2} \\
D = (2x + 7 + 9)(2x + 7 - 9)\\
D = (2x + 16)(2x -2) = 2(x + 8)(2x - 2) = 4(x+8)(x -1)\\
E = (2x + 7)^{2} - 64 \\
E = (2x + 7)^{2} - 8^{2} \\
E = (2x + 7 + 8)(2x + 7 - 8)\\
E = (2x + 15)(2x -1)

F = 4 x^{2} -40x + 100 \\
F = (2x)^{2} - 2 * 2x * 10 + 10^{2} \\
F = (2x - 10)^{2}

Bonne soirée !